Advanced methods of data protection and cryptography - Golob, Marko (ICEQ, 2007)
We are facing accelerated digitalisation in health sector which includes besides traditional administrative also increasingly operative processes. The two interface with the digitalisation of insurance and government sectors. The dependance on information technology has become all encompassing and the value of the data communicated or stored has in many ways approached to or even increased above other physical assets. Due to the very sensitive nature of its information assets the medicine sector is becoming increasingly vulnerable. One of the strongest possible means to protect the information systems has always been cryptography. This milleniums old science has moved out of the secret state »black cabinets« into the everybody's life. Mostly unaware, we are using its techniques when we identify ourselves, when we buy over internet, withdraw cash on ATM's,...Yet, despite its increasing use very few really understand how it works, what its full potential is or what its organizational requirements are. Due to its nature the Cryptography is ideally suited to digital technologies and represent the strongest possible means to protect our data, our communications, our identities and our privacy. In the last few years data protection environment has changed substantially and represents the new challanges to organizations. In the mutually interconnected world the old models of security perimeter and company centered security are giving way to end-to-end security models and client centered security. Some of the security requirements are possible to satisfy only through cryptographic techiques while others greatly benefit from them. In the following parts Author shows briefly the cryptographic tools available, how to use them and what are the organizational requirements institutions should take care of. He also touches the latest USA and EU governments initiatives aiming at increasing the security and reliability of information systems as well as their standardization efforts in the field of cryptography. The initiatives are similar in their ambition but differ in scope and detail of regulation. The author's conclusion is that the organizations in health sector are faced with demanding issues of securing their information systems. Despite its strenght cryptography should be combined with a holistic approach to security and complementary security measures. Key words: Information security, health sector, data protection, cryptography